Characterization of Neospora Caninum Microneme Protein 26 and Its Potential Use as a Diagnostic Marker for Neosporosis in Cattle - Wang, Xianmei; Song, Xingju; Yang, Jing; Liu, Qun; Liu, Jing (Frontiers in Veterinary Science, 2020)
The apicomplexan parasite Neospora caninum causes neosporosis, an illness that leads to abortion or stillbirth in cattle, causing massive economic losses to the livestock industry. Rapid and viable diagnosis is the premise of prevention and control for neosporosis. In this study, we screened a new microneme protein 26 (NcMIC26) through Western blot and mass spectrometry identification from the excretory secretion antigen (ESA) of N. caninum tachyzoites. NcMIC26 is subcellularly localized to the microneme of parasites. NcMIC26 is a specific antigen of N. caninum and has no cross-reaction with Toxoplasma gondii. Therefore, NcMIC26 has the potential to be a candidate diagnostic antigen for neosporosis. To test this hypothesis, recombinant NcMIC26 (rNcMIC26) was expressed in Escherichia. coli, and an indirect ELISA for detecting anti-N. caninum antibodies in cattle was established. Compared with that of the Indirect Immunofluorescent Antibody Test (IFAT), the positive coincidence rate of the ELISA based on rNcMIC26 was 76.53% (75/98), which was higher than that of an ELISA based on rSRS2 (66.33%), and the negative coincidence rate was 84.62% (33/39). It is noteworthy that 36 positive samples confirmed by IFAT were consistent with the rNcMIC26 ELISA but were negative by the rNcSRS2 ELISA. Our research illustrated that NcMIC26 is a dependable diagnostic marker for the serodiagnosis of N. caninum infection in cattle and could be utilized as a supplementary antigen for missed detection by NcSRS2.